2006
DOI: 10.1111/j.1600-6143.2006.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Subclinical Rejection and the Value of Protocol Biopsies

Abstract: Subclinical rejection (SCR) is diagnosed by protocol histology with a maximal prevalence occurring early after transplantation, falling to low levels by 1 year. Needle-core biopsy is safe, and the histology obtained fairly reflects subclinical immune activity. Several studies have consistently shown that SCR is associated with chronic tubulointerstitial damage, subsequent renal dysfunction and reduced graft survival. SCR is effectively treated by pulse corticosteroid therapy, although increased baseline immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 32 publications
3
133
2
3
Order By: Relevance
“…We indeed demonstrated that higher donor age and baseline histology is an independent risk factor for subclinical inflammation at 3 months, which is associated with higher increases in chronic graft damage later (19)(20)(21). It cannot be excluded that the subclinical infiltrates detected at 3 months are already present much earlier after transplantation, thus contributing to the early increase in chronic pathology, starting from implantation.…”
Section: Discussionmentioning
confidence: 68%
“…We indeed demonstrated that higher donor age and baseline histology is an independent risk factor for subclinical inflammation at 3 months, which is associated with higher increases in chronic graft damage later (19)(20)(21). It cannot be excluded that the subclinical infiltrates detected at 3 months are already present much earlier after transplantation, thus contributing to the early increase in chronic pathology, starting from implantation.…”
Section: Discussionmentioning
confidence: 68%
“…ABMR was able to predict graft loss with 38% sensitivity and 96% specificity, whereas the total i-score is able to achieve moderate sensitivities (60-80%) with acceptable losses in specificity (60-80%). (16)(17)(18)(19)26,33 (16)(17)(18). Thus, the assessment and characterization of inflammation will remain an important task, both for histopathology and transcriptomics.…”
Section: Scoring Tubulitis In Addition To the Extent Of Interstitial mentioning
confidence: 99%
“…The importance of noninvasive graft monitoring is further emphasized as subclinical rejection may occur: these cases can exclusively be detected with (invasive) surveillance or protocol biopsies (13)(14)(15)(16)(17). Currently, to our knowledge, AlloMap is the only commercially available noninvasive organ transplant monitoring test (18).…”
Section: Introductionmentioning
confidence: 99%